ANALISA KESEIMBANGAN LINI PADA DEPARTEMEN CHASSIS PT TOYOTA MOTOR MANUFACTURING INDONESIA DENGAN ALGORITMA ANT COLONY, RANK POSITIONAL WEIGHT, DAN ALGORITMA GENETIKA - Lina Gozali; Lamto Widodo; Martin Bernhard (JURNAL TEKNIK INDUSTRI, 2012)
PT . Toyota Motor Manufacturing Indonesia is a company engaged in the automotive industry. The longest cycle time can also be caused by many things, from the unequal division of labor so that the necessary analysis for the balance of the assembly line. In writing this Final analysis used the balance line is Ant Colony Algorithm, Rank Positional Weight, and Genetic Algorithms. All three methods of analysis will produce an analysis for the improvement of the assembly lines now run so as to achieve the targets that have been defined. With a high efficiency line of the balance delay of the assembly line will also be getting smaller and makes no waiting time from the operator. All the time can be optimally used to produce the product. Of the three analysis the analysis with the highest efficiency, smallest delay balance and smoothness index of the smaller to be selected as the best proposal. Analysis of this problem is best for analysis using ant colony algorithm with line efficiency 93.2%, 6.8% delay Balance and Smoothness index 45.77